Legal Architecture Beneficiary Owners at Individual Company; Reconstruction and Opportunity - Tina Amelia (Universitas Sebelas Maret, 2024)
There is a legal vacuum in the regulation of beneficiary owners of companies in Indonesia. The regulation of beneficiary owners, which should be used as a preventive supervision method, is misinterpreted as a form of repressive supervision. As a result, preventive supervision of financial transactions involving money laundering crimes is slightly slower than it should be. Another legal vacuum also occurs in relation to whether beneficiary owners share the burden of the company's debt if the company goes bankrupt. This research will be limited to individual companies only. As a new company, and targeting micro, small, and medium companies, the potential for money laundering crimes against this company is even greater. The entire description above has not been expressly regulated in Indonesian national law. This research uses normative legal research with a statutory approach and a conceptual approach. The results of the research obtained indicate that there is indeed a legal vacuum in the regulation of beneficiary owners. Therefore, it is necessary to reconstruct the regulation of beneficiary owners, so that this legal vacuum does not happen again